Antagonist capacity of local rhizobacterial isolates against Fusarium solani causing Tomato wilt in vitro (Damascus University Journal of agriculture sciences, 2025)
The research was conducted in Laboratories of Syrian National Commission for Biotechnology in Damascus and Faculty of Agricultrue at Damascus University during the years 2021 and 2022 with the aim of determination of the in vitro antagonistic ability of bacterial isolates from the rhizosphere of tomato plants in protected cultivation in the Syrian coast against Fusarium solani causing Tomato wilt. Six bacterial isolates (A12, B22, C33, F63, I91, J02) were obtained from healthy tomato roots, one isolate (K11) from the soil, and one isolate (RIZN) from the periphery of the root nodules of Trifolium purpureum.The isolates were identified according to several biochemical tests, and it turned out that four of them (A12, B22, C33, F63) belong to the species Pseudomonas fluorescens and the other four (I91, J02, K11, RIZN) belong to the Bacillus cereus. The antigenicity of these bacterial isolates was tested with Fusarium solani in the laboratory by two methods, the Sectors method using bacterial suspensions and Well-Plate Assay method using bacterial filtrate.In both methods, the bacterial isolates belonging to the Bacillus cereus gave the best antagonistic ability, and the RIZN isolate excelled, giving an 43.8% inhibition rate, and The antagonistic distance between the fungal growth and the well was 36.3 mm.
Keywords: Fusarium Wilt; Fusarium Solani; Pseudomonas Fluorescens; Bacillus Cereus; Antagonist; Syria